Evaluation of the Environmental Quality of a Cemetery using the Method of the Peir Matrix - Case Study - Lins, Eduardo Antonio Maia; Rios, Olga Marine; Fernandes Paz, Diogo Henrique; Pessoa Melo, Danielle de Castro; Maia Lins, Adriana da Silva Baltar (International Journal of Advanced Engineering Research and Science, 2022)
Cemeteries are potential sources of environmental impact because they do not follow the various standards established by CONAMA. Most of them are not supervised or undergo periodic maintenance, being responsible for polluting the soil, subsoil and also reaching numerous groundwater from the areas where they were installed, considerably affecting the health of the local population. The study took place in the várzea cemetery, in the city of Recife, state of Pernambuco. The choice of this potential source of contamination stems from the scarcity of studies on the subject, especially in the State of Pernambuco. Local visits related to local information suggest not only non-compliance with the rules, but also possible pollution and contamination of soil and free aquifer. Therefore, the present research aims to investigate the environmental quality of the Várzea cemetery using the Pressure-State-Impact-Response Matrix (PEIR Matrix). The methodology used was the literature review, on-site visits in order to verify compliance with the legislation as well as the construction of a Matrix, also based on an analysis of soil quality. Considering the data obtained with the particle size analysis, it was verified that the sediments, in the cemetery area, showed predominance of sand grains in the surface layer of the terrain. It was possible to conclude through the matrix that the cemetery presents itself with low environmental quality and may be generating negative environmental impacts of great proportions.